Sharenting – skala i wielowymiarowość zjawiska (nierozważnego) ujawniania przez rodziców informacji o dzieciach w mediach społecznościowych - Bożena Chrostowska (Problemy Wczesnej Edukacji)
The scope of the article is to discuss the issue of the parents sharing the information about their children in social media. Basing on literature and researches review, the scale of sharenting phenomenon was introduced. Its different types were discussed and its chosen legal, ethical and social aspects were characterized. The risks (i.e. identity theft and exposing children to cyberviolence) and rewards (i.e. sharing the experience, seeking and providing support) of such parents’ activity in the Internet were presented as well. Sharenting generates dilemmas connected with finding the balance between the parents’ right to express freely and the child’s right to have privacy, dignity and identity. There is a need of educational actions, directed to both parents and society, about the children’s security and safety of their privacy in the Internet.